The Effectiveness of Applied Behavior Analysis in Improving Academic Participation among Children with Autism in Inclusive Schools - Tri Gunadi (International Journal Labs, 2026)
Children with Autism Spectrum Disorder often experience difficulties in maintaining attention, following instructions, and completing academic tasks in inclusive classroom settings. These difficulties can limit their academic participation and engagement during learning activities. This study aimed to examine the effectiveness of Applied Behavior Analysis intervention in improving academic participation among children with Autism Spectrum Disorder in inclusive schools. The study used a single subject experimental design consisting of baseline and intervention phases. Behavioral observations were conducted to measure indicators of academic participation, including following instructions, completing tasks, maintaining attention, and sitting during learning activities. The intervention was implemented for ten sessions using reinforcement, prompting, and task analysis strategies. The results showed a significant improvement in academic participation after the implementation of the intervention. The average participation score increased from 6.8 during the baseline phase to 15.2 during the intervention phase. These findings indicate that Applied Behavior Analysis is effective in increasing academic participation among children with autism spectrum disorder in inclusive educational settings